Simple expressions for computing impedance matrix of rectangular planar microwave circuits - Abdul Hadi, Putri Irene Alia (2003)
The paper gives details of the mathematical derivations needed and the algorithm for computation of impedance matrix for a rectangular microstrip circuit. The software developed is used to compute the impedance matrix for a circuit configuration for which the results are known. The computed results are in very good agreement with the results already known.